2016
DOI: 10.4103/2153-3539.186909
|View full text |Cite
|
Sign up to set email alerts
|

Comparing whole slide digital images versus traditional glass slides in the detection of common microscopic features seen in dermatitis

Abstract: Background:The quality and limitations of digital slides are not fully known. We aimed to estimate intrapathologist discrepancy in detecting specific microscopic features on glass slides and digital slides created by scanning at ×20.Methods:Hematoxylin and eosin and periodic acid–Schiff glass slides were digitized using the Mirax Scan (Carl Zeiss Inc., Germany). Six pathologists assessed 50–71 digital slides. We recorded objective magnification, total time, and detection of the following: Mast cells; eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
(42 reference statements)
5
25
0
Order By: Relevance
“…18,28,32 For example, identifying microorganisms or granulocytic inflammation and counting mitotic figures may benefit from higher magnifications and thereby higher digital resolution. 18,28,30 However, Vyas et al 33 concluded from their results that WSI scanned at 200× magnification are adequate to detect most histopathologic features of inflammatory skin disease in comparison with glass slides, with only some limitations for detecting cellular features. Also, intraobserver concordance between 200× and 400× magnification of WSI of human breast needle biopsies did not differ significantly in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…18,28,32 For example, identifying microorganisms or granulocytic inflammation and counting mitotic figures may benefit from higher magnifications and thereby higher digital resolution. 18,28,30 However, Vyas et al 33 concluded from their results that WSI scanned at 200× magnification are adequate to detect most histopathologic features of inflammatory skin disease in comparison with glass slides, with only some limitations for detecting cellular features. Also, intraobserver concordance between 200× and 400× magnification of WSI of human breast needle biopsies did not differ significantly in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining features showed significantly greater degrees of discordance. A similar recent study by Vyas et al evaluating the efficacy of teledermatopathology, including the detection of histopathologic features, found that DS scanned at ×20 were sufficient for detection of histopathologic features routinely encountered in dermatitis cases, although less efficient than GSs . In that study, high intraobserver concordance was observed for particular histopathologic features such as sebocytes and fungal bodies, while poor to fair concordance was seen for other features including melanin in the epidermis, plasma cells and neutrophils.…”
Section: Discussionmentioning
confidence: 66%
“…4 found that DS scanned at ×20 were sufficient for detection of histopathologic features routinely encountered in dermatitis cases, although less efficient than GSs. 19 In that study, high intraobserver concordance was observed for particular histopathologic features such as sebocytes and fungal bodies, while poor to fair concordance was seen for other features including melanin in the epidermis, plasma cells and neutrophils. Furthermore, 1 such histopathologic feature (sebocytes) was more accurately detected on DS as compared with traditional GSs.…”
Section: Discussionmentioning
confidence: 76%
“…9 Another hurdle is that dermatopathologists may be initially slower in viewing digitized images, though speed increases with user experience. 10,11 Several differences in feature detection have also been noted, such as decreased ability to detect eosinophils and gram-positive bacteria using WSI; however, these limitations can be sufficiently corrected by scanning slides with special stains for microorganism detection at higher resolution. 12 The large-scale switch to telework across the country has helped keep Americans safe and highlighted benefits to the environment, while prior research on working from home has shown increased productivity and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%